Tectonic controls on Miocene sedimentation in the Southern Taranaki Basin and implications for New Zealand plate boundary deformation. (29th January 2019) - Bull, Suzanne; Nicol, Andrew; Strogen, Dominic; Kroeger, Karsten F.; Seebeck, Hannu S.
Abstract: Miocene strata in the southern Taranaki Basin (STB), up to 3 km thick, provide a distal record of erosion associated with plate boundary deformation in New Zealand. 2D and 3D seismic reflection data tied to drillhole stratigraphy have been used to constrain four main phases of basin development. These are: (a) Early Miocene (22–19 Ma) subsidence, dominantly bathyal water depths and deposition of minor submarine fans along the eastern basin margin. (b) Middle Miocene (19–14 Ma) widespread submarine fan deposition on a bathyal basin floor in the central STB. (c) Rapid Middle–Late Miocene (14–7 Ma) progradation of the shelf break northwards across the STB. (d) Widespread uplift and erosion of the STB during the latest Miocene–Pliocene (7–4.5 Ma). Bathyal water depths and fan deposition in the Early Miocene were influenced by vertical motions on major reverse faults and regional subsidence produced by subduction of the Pacific plate beneath northern New Zealand. Subsequent submarine fan deposition and northward shelf‐break progradation reflect increasing input of terrigenous material, primarily eroded from an uplifting region to the south of the STB. Sedimentation patterns in the STB are consistent with the age and locations of conglomerates deposited in onshore West Coast basins, related to this uplift and erosion. Sediment transport in the West Coast region was mainly parallel to NNE trending active reverse faults, and in the STB was perpendicular to the NE‐SW orientated shelf break, especially from ca. 14–7 Ma, when sedimentation rates exceeded fault‐displacement rates. Increases in sedimentation rates in the STB coincide with regional increases in the rates of shortening that appear to reflect plate boundary‐wide events and have been attributed to, or correlated with, increases in the plate convergence rate. Miocene sedimentation patterns in the STB thus reflect both intra‐basinal deformation and tectonic signals from the wider developing New Zealand plate boundary.